Study on the mechanical properties of an inerter friction damper - Ruixin Hu; Weibing Xu; Jin Wang; Xiuli Du; Xiaomin Huang; Qingchuang Guo; Keming Pan; Dingqing Feng; Cheng Wang (Soil Dynamics and Earthquake Engineering, 2026)

Antagonistic effects of temperature and salinity on total dimethylsulfoniopropionate (DMSPt) production in a river-dominated bay during extreme winter events - Lingxiao Li; Jing Sun; Zhengguo Cui; Tao Jiang; Zhenhao Liu; Keming Qu; Hongsheng Wang; Qingjing Hu; Hongwu Cui; Shenghui Zhang (Estuarine, Coastal and Shelf Science, 2026)

Corrigendum to “Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture” [Chem. Eng. J. 527 (2026) 171623] - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Optimizing shrimp growth and water quality in constructed wetland recirculating aquaculture systems: Effects of stocking density and shrimp size - Meimei Hu; Yanyan Wang; Jianlei Chen; Hongwu Cui; Shengmin Zhu; Tongtong Jin; Keming Qu; Zhengguo Cui (Aquaculture, 2026)

Rapid and scalable synthesis of CALF-20 extrudates for VPSA-based CO2 capture - Jifu Wang; Jianyu Sun; Lina Zhang; Guoping Hu; Gaobing Sheng; Keming Chen; Tianyang Zhu; Yufeng Hao; Hongyu Zhao; Baodeng Wang; Wei Wei; Nannan Sun (Chemical Engineering Journal, 2026)

Carnitine content and its influencing factors in marine animals collected from China’s offshore region and the Northwest Pacific Ocean - Yufeng Gao; Zhengguo Cui; Jianwei Li; Keming Qu; Qingkui Wang; Lanlan He; Xiangtao Liu; Xiner Zhao; Liuyizhi Zhang; Lingxiao Li; Ying Bai; Fangqun Dai; et al. (Acta Oceanologica Sinica, 2025)

Numerical and experimental study of CO2 jet impingement on curved surfaces with different phases - Qian Chen; Laibin Zhang; Jianchun Fan; Yunpeng Yang; Keming Hu; Yang Fu (Process Safety and Environmental Protection, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Ecological risk assessment for BDE-47 in marine environment based on species sensitivity distribution method - Ying Bai; Ruijie Ma; Zhengguo Cui; Liping Liu; Dongsheng Ding; Qingjing Hu; Bin Xia; Zhaochuan Li; Haibo Zhang; Keming Qu (Marine Environmental Research, 2025)

Effects of heavy metal concentration on zooplankton community composition and abundance in the Yellow Sea coast - Chenshi Weng; Dongsheng Ding; Zhengguo Cui; Keming Qu; Yuqiu Wei; Haiyan Hu (Marine Environmental Research, 2025)

Optical characteristic of dissolved organic matter polar fractions by spectrum technologies and the relationship with indirect photodegradation of ofloxacin - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Qingjing Hu; Yuqiu Wei; Lin Zhu; Keming Qu; Rongguo Su (Journal of Environmental Chemical Engineering, 2024)

Purification of seawater aquaculture using constructed wetlands in a recirculating aquaculture system for Pacific white shrimp (Litopenaeus vannamei) and analysis of microbial community structure - Yanyan Wang; Meimei Hu; Jianlei Chen; Hongwu Cui; Shengmin Zhu; Tongtong Jin; Keming Qu; Zhengguo Cui (Journal of Water Process Engineering, 2024)

A comparative analysis of growth and nutritional quality of the hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) in a simulated pond system and a recirculating aquaculture system - Yingsha Qu; Zhendong Yin; Xiangyu Fan; Haiyan Hu; Hongwu Cui; Zhengguo Cui; Keming Qu; Hao Li (Frontiers in Marine Science, 2024)
Groupers, as a popular economic fish species, are now more frequently cultured in land-based facilities, however, traditional pond-farming methods are plagued by frequent disease outbreaks, unstable economic benefits, and environmental pollution. To explore a new farming mode for a grouper, an 80-day cultivation experiment was conducted using both a simulated pond system (SPS) and a recirculating aquaculture system (RAS). The research aims to evaluate the growth performance, health (pathogenic bacteria, intestinal microbiota), off-flavor compounds (geosmin, 2-methylisoborneol), and nutritional component (amino acids, fatty acid composition and content) of a hybrid grouper ( Pinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ ) under different aquaculture systems. The results showed that the hybrid grouper in a RAS exhibited better growth performance; the concentration of Vibrio in the fish tissue in the RAS was significantly lower than that in the SPS. Moreover, the content of fresh amino acids in the RAS was significantly higher, and the levels of saturated fatty acids (SFAs) and ω-6 polyunsaturated fatty acids (ω-6PUFAs) were significantly higher in the RAS. This finding indicates the superior flavor and nutritional value of the grouper. These results prove that the RAS is suitable for the widespread cultivation of grouper.

The characteristics of trimethylamine N-oxide content in different classes of marine animals over the coastal and offshore areas of China - Ning An; Hongsheng Wang; Jianwei Li; Lanlan He; Yufeng Gao; Lingxiao Li; Qingkui Wang; Zhengguo Cui; Keming Qu; Qingjing Hu (Marine Pollution Bulletin, 2023)

Fine mapping and candidate gene analysis of qSB12YSB, a gene conferring major quantitative resistance to rice sheath blight - Yu Wang; Quanyi Sun; Jianhua Zhao; Taixuan Liu; Haibo Du; Wenfeng Shan; Keting Wu; Xiang Xue; Chao Yang; Jun Liu; Zongxiang Chen; Keming Hu; et al. (Theoretical and Applied Genetics, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Spatial distribution and potential ecological risk assessment of heavy metals in the sediments of fishing ports along the coasts of the Yellow Sea and Bohai Sea - Hongsheng Wang; Qingjing Hu; Dongsheng Ding; Lingxiao Li; Ning An; Keming Qu; Chuanxia Liu; Mingying Zhou; Zhengguo Cui (Marine Pollution Bulletin, 2023)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

The characteristics of CDOM structural composition and the effect on indirect photodegradation of sulfamerazine - Ying Bai; Zhengguo Cui; Dongsheng Ding; Chenfei Hong; Hongwu Cui; Qingjing Hu; Mingying Zhou; Keming Qu (Science of The Total Environment, 2023)

AtDIV2, an R-R-type MYB transcription factor of Arabidopsis, negatively regulates salt stress by modulating ABA signaling - Qing Fang; Qiong Wang; Hui Mao; Jing Xu; Ying Wang; Hao Hu; Shuai He; Junchu Tu; Chao Cheng; Guozheng Tian; Xianqiang Wang; Xiaopeng Liu; et al. (Plant Cell Reports, 2018)

Identification and characterization of SHORTENED UPPERMOST INTERNODE 1, a gene negatively regulating uppermost internode elongation in rice - Li Zhu; Jiang Hu; Keming Zhu; Yunxia Fang; Zhenyu Gao; Yinghong He; Guangheng Zhang; Longbiao Guo; Dali Zeng; Guojun Dong; Meixian Yan; Jian Liu; et al. (Plant Molecular Biology, 2011)

Overexpression of Citrus junos mitochondrial citrate synthase gene in Nicotiana benthamiana confers aluminum tolerance - Wei Deng; Keming Luo; Zhengguo Li; Yingwu Yang; Nan Hu; Yu Wu (Planta, 2009)